2022
DOI: 10.3390/vision6030050
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Squamous Neoplasia: A 12-Month Prospective Evaluation of Incidence in Waikato, New Zealand

Abstract: Ocular surface squamous neoplasia (OSSN) has a high incidence in the southern hemisphere. This prospective study evaluated the incidence of OSSN in the Waikato region of New Zealand. All patients presenting with pterygium or conjunctival lesions in the Waikato region in 2020 were included. All surgeons in the region were asked to send all conjunctival and corneal specimens excised for histopathologic examination. The primary outcome measure was the incidence of OSSN. Eighty-eight percent of all excised specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
2
0
0
Order By: Relevance
“…Higher levels of UV-B exposure in Malawi, Thailand, and India (with population-weighted average daily ambient UV radiation levels of 5,019 J/m 2 , 4,862 J/m 2 , and 4,514 J/m 2 , respectively) seem to correlate with the higher proportions of invasive disease in these regions, while Taiwan (2,908 J/m 2 ), which has similar levels of UV-B radiation to our population (3,206 J/m 2 ) had a comparable low rate of invasive disease to that of our study [12, 22, 26‒28]. However, this trend did not hold across all countries, as the recent New Zealand-based study by Hossain et al (2022) had higher rates of invasive disease despite substantially lower UV-B radiation (2,487 J/m 2 ), while Shields et al (2017) found significantly higher rates of invasive disease despite similar levels of radiation exposure (2,736 J/m 2 ) [11, 18].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Higher levels of UV-B exposure in Malawi, Thailand, and India (with population-weighted average daily ambient UV radiation levels of 5,019 J/m 2 , 4,862 J/m 2 , and 4,514 J/m 2 , respectively) seem to correlate with the higher proportions of invasive disease in these regions, while Taiwan (2,908 J/m 2 ), which has similar levels of UV-B radiation to our population (3,206 J/m 2 ) had a comparable low rate of invasive disease to that of our study [12, 22, 26‒28]. However, this trend did not hold across all countries, as the recent New Zealand-based study by Hossain et al (2022) had higher rates of invasive disease despite substantially lower UV-B radiation (2,487 J/m 2 ), while Shields et al (2017) found significantly higher rates of invasive disease despite similar levels of radiation exposure (2,736 J/m 2 ) [11, 18].…”
Section: Discussionsupporting
confidence: 56%
“…Conversely, Taiwan had a comparable higher mean age of diagnosis to our study, reflecting the similar levels of UV-B radiation in that region [12]. However, recent data from New Zealand contradict this trend, as Hossain et al [18] (2020) had a substantially lower mean age of diagnosis than our cohort, despite exposure to lower levels of UV-B radiation.…”
Section: Discussionsupporting
confidence: 53%